Exploring Biofouling Control by the California Sea Cucumber (Apostichopus californicus) in Integrated Multi-Trophic Aquaculture (IMTA) with Organic Chinook Salmon (Oncorhynchus tshawytscha) - Emaline M. Montgomery; Barb L. Cannon; Christopher M. Pearce (Fishes, 2023)
The growth of biofouling on aquaculture infrastructure is a universal challenge. Standard industry practices to remove biofouling in finfish aquaculture typically include in situ net cleaning via power washing. Since those cleaning practices can be potentially harmful to fish-gill health and expensive, development of other non-toxic biofouling controls is an industry priority. Deposit-feeding sea cucumbers are potentially well suited for biofouling control due to their feeding mechanism, but remain relatively untested in this capacity. We examined the use of California sea cucumbers (Apostichopus californicus) to control biofouling on cages containing adult Chinook salmon (Oncorhynchus tshawytscha) at a commercial farming operation. Four cage types were established: cages with salmon and sea cucumbers, cages with salmon only, cages with sea cucumbers only, and cages without either species. Results showed that the sea cucumbers actively fed on biofouling when salmon were absent (~16% cleaner on average) but preferred to consume uneaten feed/faeces at the bottom of the cages, neglecting the biofouling, when the salmon were present. It is hypothesized that biofouling control in cages with salmon may be possible with an increased density of sea cucumbers. This is the first study to examine the use of sea cucumbers as a direct net biofouling control agent with adult fish. Our results will be beneficial for industry to develop standard operating procedures for using California sea cucumbers as a biofouling control and could contribute to the development of a management framework for sea cucumber/salmon integrated multi-tropic aquaculture.